Reform of Criminal Justice Systems: A Comparative Study of Restorative Justice in Indonesia and the Netherlands - Mohammed Abdu Rehany (ILAW, 2025)
The reform of criminal justice systems has increasingly shifted toward more humane and participatory approaches, particularly through the adoption of restorative justice. This study aims to analyze and compare the implementation of restorative justice in Indonesia and the Netherlands as part of broader criminal justice system reforms. The research employs a normative legal method with a comparative approach, examining legal frameworks, institutional mechanisms, and practical applications in both countries. The findings reveal that Indonesia applies restorative justice in a more flexible and culturally embedded manner, emphasizing social harmony and community-based resolution. However, its implementation remains fragmented and largely dependent on the discretion of law enforcement authorities. In contrast, the Netherlands demonstrates a more structured and institutionalized approach, supported by clear legal regulations, professional mediation services, and stronger protection of victims’ rights. Both countries share a common objective of reducing reliance on punitive measures, improving access to justice, and restoring social relationships. Nevertheless, differences in legal certainty, institutional capacity, and empirical evaluation highlight the need for further development, particularly in Indonesia. This study concludes that an integrative model combining legal rigor with socio-cultural adaptability is essential for achieving an effective and equitable criminal justice system.